Delayed intensive care unit admission is associated with increased mortality in patients with cancer with acute respiratory failure. Issue 8 (August 2013) - Mokart, Djamel; Lambert, Jérôme; Schnell, David; Fouché, Louis; Rabbat, Antoine; Kouatchet, Achille; Lemiale, Virginie; Vincent, François; Lengliné, Etienne; Bruneel, Fabrice; Pene, Frederic; Chevret, Sylvie; et al.
Abstract Acute respiratory failure (ARF) is the leading reason for intensive care unit (ICU) admission in patients with cancer. The aim of this study was to identify early predictors of death in patients with cancer admitted to the ICU for ARF who were not intubated at admission. We conducted analysis of a prospective randomized controlled trial including 219 patients with cancer with ARF in which day-28 mortality was a secondary endpoint. Mortality at day 28 was 31.1%. By multivariate analysis, independent predictors of day-28 mortality were: age (odds ratio [OR] 1.30/10 years, 95% confidence interval [CI] [1.01–1.68], p = 0.04), more than one line of chemotherapy (OR 2.14, 95% CI [1.08–4.21], p = 0.03), time between respiratory symptoms onset and ICU admission > 2 days (OR 2.50, 95% CI [1.25–5.02], p = 0.01), oxygen flow at admission (OR 1.07/L, 95% CI [1.00–1.14], p = 0.04) and extra-respiratory symptoms (OR 2.84, 95%CI [1.30–6.21], p = 0.01). After adjustment for the logistic organ dysfunction (LOD) score at admission, only time between respiratory symptoms onset and ICU admission > 2 days and LOD score were independently associated with day-28 mortality. Determinants of death include both factors non-amenable to change, and delay in ARF management. These results suggest that early intensive care management of patients with cancer with ARF may translate to better survival.